THE SENASNA MANAGEMENT IN PHRA NAKHON SRI AYUTTHAYA PROVINCE USED ITTI BATH DHAMMA - Sirivaddhano, Phrakhruwinaitron Sirichet (Journal of MCU Nakhondhat, 2021)
Buddhism Has made great progress Most of the people practice Buddhism. And Buddhism has affected the Thai culture of life. Causing many valuable architectural constructions with the strength of faith in Buddhism, Buddhists know to join forces together to create a more beautiful Thawornwatthu. To symbolize Buddhism In particular, religious places such as the church of Phra Stupa, Mondop, Prasat, Hall, Hall, Bell Tower, kuti, etc. are all the center of Buddhism of all sexes and ages. Is a place for rest and practice and learn about the traditions of living in a Buddhist way Including the practice of traditional culture as well Therefore, matters relating to the temple from the past to the present Often involved in the matter of the arrangement. Because it is both a materialistic aspect and places of worship that are related to self - practice in Buddhism Especially the management of affection to be in accordance with good management principles, based on the principle of “Ittibaht, Dharma” to be used in management at the same time. The principle of dharma consists of: 1) The principle of satisfaction or have a love of organization (chanting) 2) Principle of perseverance and effort or commitment Patience in management (persistence) 3) The intention. Or mindfulness Concentrate with consciousness (Chitta). 4) Principles of consideration and reflection. Or always check (Wimangsa), so the 4 management principles are the principles of conduct to lead to success. Including self - management Manage people and manage work Therefore, the management of Senasana in Phra Nakhon Si Ayutthaya Province The same It is necessary to apply the principle of virtue and Dharma to apply in the management of sentiment to be orderly, hygienic and beneficial to Buddhists.